Kambaata children’s songs and word games: Or what can we learn about the grammar of Kambaata by analysing marginal literature genres? - Treis, Yvonne (Afrikanistik online, 2012)
The present article analyses children’s songs and word games of the Cushitic language Kambaata and follows up on the question whether this text genre can contribute useful data for a grammatical analysis of this little known language. The corpus of nine texts, which are glossed, translated and annotated, constitute the core of this article. Recordings of the texts are made available.
Keywords: Kambaata; Kinderlieder; Literaturgenre; Wortspiele; children's songs; word games